Characteristics, indications and complications in patients undergoing permanent pacemaker implantation: a single centre study - Bhat, Sanjeev; Kumar, Dharminder; Parimoo, Aditi (International Journal of Research in Medical Sciences, 2018)
Background: To determine the demographic details, indications, type of pacemakers and complications in patients undergoing the permanent pacemaker implantation. Methods: This was a single-center, retrospective study conducted in at a tertiary-care center in India. The records of 200 patients who had undergone implantation of permanent pacemakers in the period of May 2016 to April 2018 were reviewed. Results: Total 200 patients with mean age of 67 years were paced. Of these 120 (60%) were males. The mean duration of hospital stay was 6.5 days. Sinus node disease (105 patients, 52.5%) was the most common indication for permanent pacemaker insertion. Single chamber (VVIR) pacing mode (125 patients, 62.5%) was found to be the most common pacing mode used for pacemaker insertion. Among the 200 patients complications were observed in 8 patients (4%). Of these 8 patients, pneumothorax (4 patients, 2%) was found to be the most common complication for permanent pacemaker implantation followed by local site infection (1 patient, 0.5%). Only 1 patient (0.5%) died during the observation period of the study. Conclusions: Geriatric population with male predominance have observed to commonly undergo permanent pacemaker implantation. Sinus node disease in the elderly patients is the most common indication for cardiac pacing followed by atrioventricular block. Single chamber (VVIR) pacing mode is commonly used followed by dual chamber (DDDR) due to economic reasons in India. Pacemaker implantation is a relatively safe procedure with a low complication rate.